Do mentoring programmes influence women’s careers in the health and medical research sector? A mixed-methods evaluation of Australia’s Franklin Women Mentoring Programme - Rohina Joshi; Amy Vassallo; Melina Georgousakis (BMJ Open, 2021)
Objectives It is known that women are under-represented in senior positions within the health and medical research sector. The Franklin Women Mentoring Programme (Programme) is a professionally facilitated, cross-organisational initiative designed to support career development for mid-career women. The objective of this study was to evaluate Programme outcomes reported by participants 12 months following its formal conclusion.Design Explanatory sequential mixed-methods study design using a cross-sectional survey and semi-structured interviews.Setting Health and medical research institutes in Sydney, Australia.Participants Health and medical researchers from the 2018 Programme.Primary and secondary outcome measures Changes in knowledge, skills, behaviours and research metrics directly attributed to Programme participation.Results A total of 50 mentors and mentees participated in the cross-sectional survey (68% of the total cohort) and 14 mentors and mentees participated in the interviews. All reported changes to their knowledge, skills, behaviours and research metrics which were directly attributed to participation in the Programme. This included changes in knowledge and skills to be more inclusive (96% mentees, 83% mentors), resilience (88% mentees, 67% mentors), ability to have difficult workplace conversations (88% mentees, 71% mentors) and improvements in supervisory and team management (82% mentees, 75% mentors) skills. Positive impacts on promotions and grant opportunities were also reported. All evaluation participants believed this Programme was a worthwhile initiative for their workplaces to invest in.Conclusion Participation in this cross-organisational, professionally facilitated, structured mentoring programme has led to positive outcomes for mentees, as well as mentors. Reported outcomes indicate the Programme is meeting its aims to support the career development of mid-career women in health and medical research, while facilitating a more inclusive workforce.